2002
DOI: 10.1002/1521-4087(200206)27:3<150::aid-prep150>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Burning Behavior of Cryogenic Solid Propellants

Abstract: Cryogenic Solid Propellant (CSP)‐technology is a new approach to develop more powerful rocket motors. CSPs include the advantages of classical solid propellants to save weight as well as those of a high energy content and safety of modern liquid propellants. The charges consist of liquid and/or gaseous fuels and oxidizers, both frozen. Two main versions of CSP‐technology can be realised: 1. Mono‐CSPs show the burning behavior of solid propellants. Experiments with mono‐CSPs have been carried out under inert pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Thus, simultaneous combustion wave speed (R) and pressure measurements allow us to plot the dependence of R [m s À1 ] on pressure P [MPa] for slow combustion regime (Figure 9(b)). The obtained data were fitted to the power law dependence for ballistic propellant, also well known as Vieilles law [19],…”
Section: Combustion Wave Speed Measurementsmentioning
confidence: 99%
“…Thus, simultaneous combustion wave speed (R) and pressure measurements allow us to plot the dependence of R [m s À1 ] on pressure P [MPa] for slow combustion regime (Figure 9(b)). The obtained data were fitted to the power law dependence for ballistic propellant, also well known as Vieilles law [19],…”
Section: Combustion Wave Speed Measurementsmentioning
confidence: 99%
“…In 1990s, B. Voslamber,M .V oslamber, and R. E. Lo discussed the feasibility of CSP and concluded that CSP was technically feasible on any aspects for practical application [ 5,6].S ince the beginning of 21stc entury, the research activities on CSP have enteredi nto av igorous period. Many issuesc overed by CSP,i ncluding theoretical performance [7,8],p ropellant ingredients [8],g rain structures and preparationt echnique [9][10][11],c ombustion characteristics [12][13][14][15][16], motor designa nd experiments [17,18], etc. have been investigated deeply.I nt heser esearches, H 2 O 2 was selected as oxidizer ingredient of CSP due to its high oxygenc ontent, non-toxicity,a nd simplicity of operation.AlthoughC SP has the advantageso fb oth solid and liquid propellants, it also has notable limitations.…”
mentioning
confidence: 99%